2022
DOI: 10.21037/atm-22-1261
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TLR-4 on the proliferation and differentiation of bone mesenchymal stem cells and its relationship with the Wnt signal transduction pathway during bone nonunion

Abstract: Background: Bone nonunion is a special fracture complication that occurs in about 5% to 10% of cases.This type of fracture is difficult to heal, and causes great pain to patients and affects their quality of life. The mechanism of bone nonunion is not clear. In our study, we investigated the influence of Toll-like receptor (TLR)-3, TLR-4, and Wnt signaling pathways on the occurrence of bone nonunion.Methods: Firstly, we established a Sprague Dawley (SD) rat model of femoral nonunion, and detected the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition to CGRP, SP has been implicated in aspects of bone healing, including angiogenesis. Models of fracture nonunion have revealed a substantial reduction in the mRNA expression of both CGRP and SP [ 40 ]. Both CGRP and SP are increased in the first 24 h after fracture [ 41 ].…”
Section: Peripheral Nervous System Regulation Of Fracture Healingmentioning
confidence: 99%
“…In addition to CGRP, SP has been implicated in aspects of bone healing, including angiogenesis. Models of fracture nonunion have revealed a substantial reduction in the mRNA expression of both CGRP and SP [ 40 ]. Both CGRP and SP are increased in the first 24 h after fracture [ 41 ].…”
Section: Peripheral Nervous System Regulation Of Fracture Healingmentioning
confidence: 99%
“…This was confirmed by Mei et al, the 10 ng/mL LPS group of m-BMSCs demonstrated the lowest expression of ALP, Col I, and RUNX2, as well as the least osteogenesis. The downregulated expression levels of β-catenin and c-Myc, core proteins of the canonical Wnt signaling pathway were also observed, indicating the positive effects of the Wnt signaling pathway on the proliferation and differentiation of BMSCs ( Mei et al, 2022 ). He and others showed contradictory results.…”
Section: Tlr Activation On Osteogenic Differentiation Potential Of Mscsmentioning
confidence: 99%
“…14 A recent study indicates that TLR4 inhibits the proliferation and differentiation of bone mesenchymal stem cells. 15 However, the effect of SVF-gel on diabetes ulcers and its potential mechanism are not clear. In this study, we constructed a diabetic ulcer rat model to investigate the mechanism of SVF-gel on the diabetic ulcers and peripheral nerves, in order to provide new ideas for the clinical treatment of diabetic ulcers and peripheral nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%